Strategic Map of University Incubation Center - Faraz, Nahiyah Jaidi; Indartono, Setyabudi; Siswantoyo, Siswantoyo; Liu, Jane S.C. (Jurnal Economia, 2021)
Abstract: This study is aimed to investigate the Strategic Map of the Incubator center. The business incubation process can vary from one incubator to another. This research extends the previous works to improve the solution business incubator problems in Indonesia heading their competitive advantages heading to the global market compared to the Taiwan cases. This study investigates the different types of business incubator strategies for Indonesia and Taiwan cases by using quantitative and qualitative with the primary that had been collected through surveys and observations. The Result shows that Chaoyang Business Incubation Center (CBIC) and Business Incubator LPPM UNY have quite different patterns of their strategies. The Business Support Model Represent CBIC is program demand: Entrepreneur-initiated, whereas LPPM one is program supply: Incubator-initiated. The Business Incubator LPPM UNY is likely to be more active than BCIC. However, CBIC seems to promote entrepreneurs more actively rather than Business Incubator LPPM UNY. Keywords: Strategic Map, Incubation Center, Indonesia, Taiwan Peta Strategis Pusat Inkubasi Universitas Abstrak: Penelitian ini bertujuan untuk menyelidiki peta strategis dari pusat inkubator. Proses inkubasi bisnis dapat bervariasi dari satu inkubator ke inkubator lainnya. Penelitian ini memperluas karya-karya sebelumnya untuk meningkatkan masalah inkubator bisnis solusi di Indonesia yang mengarah keunggulan kompetitif mereka menuju pasar global dibandingkan dengan kasus Taiwan. Penelitian ini menyelidiki berbagai jenis strategi inkubator bisnis untuk kasus Indonesia dan Taiwan dengan menggunakan kuantitatif dan kualitatif dengan primer yang telah dikumpulkan melalui survei dan observasi. Hasil penelitian menunjukkan bahwa Pusat Inkubasi Bisnis Chaoyang (CBIC) dan inkubator bisnis LPPM UNY memiliki pola strategi mereka yang sangat berbeda. Model pendukung bisnis merupakan CBIC adalah permintaan program: wirausaha dimulai, sedangkan LPPM satu adalah pasokan program: inisiasi inkubator. Inkubator bisnis LPPM UNY kemungkinan akan lebih aktif daripada BCIC. Namun, CBIC tampaknya mempromosikan wirausahawan lebih aktif daripada inkubator bisnis LPPM UNY. Kata kunci: Peta Strategis, pusat Inkubator, Indonesia, Taiwan